Faktor-Faktor yang Mempengaruhi Konsumen dalam Memilih Coffe Shop Modern pada Masa Pandemi Covid-19 di Kecamatan Syiah Kuala Kota Banda Aceh - Fadhilah Rany Shallaby; T. Makmur; Otto Nur Abdullah (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
The increasingly widespread presence of modern coffee shops is triggered by the changes in lifestyle of urban communities in Indonesia which trigger changes in coffee consumption patterns, where consumers now consider coffee as a lifestyle. The increase in the number of modern coffee shop businesses in Banda Aceh City proves that the coffee buyers in Banda Aceh City are very large. Therefore, it is important for modern coffee shop business owners to have their own advantages in the eyes of consumers compared to their competitors in order to gain customer loyalty. A total of 100 samples were taken from the 5 largest and most popular modern coffee shops in Syiah Kuala District, Banda Aceh City. Based on the research data, it is obtained that together the variables Product (X1), Price (X2), Place (X3), Service (X4), Promotion (X5), and Health Protocol (X6) have a significant influence on Consumer Decisions in choosing a modern coffee shop during the Covid-19 pandemic in Syiah Kuala District.